Potential Influence of Parasitic Diseases as Protective Agents from Infection with Pandemic COVID-19 - Mohammad Abd AL-Khaliq, Israa (AL-Kindy College Medical Journal, 2022)
Parasitic diseases can affect infection with COVID-19 obviously, as protective agents, or by reducing severity of this viral infection. This current review mentions the common symptoms between human parasites and symptoms of COVID-19, and explains the mechanism actions of parasites, which may prevent or reduce severity of this viral infection. Pre-existing parasitic infections provide prohibition against pathogenicity of COVID-19, by altering the balance of gut microbiota that can vary the immune response to this virus infection.